A Stiffness-based Approach to Analyze the Fire Behaviour of Cross-Laminated Timber Floors. Issue 2 (1st May 2017) - Franzoni, Lorenzo; Dhima, Dhionis; Lyon, Florent; Lebée, Arthur; Foret, Gilles
Abstract: In the present paper, the experimental deflection of cross-laminated timber floors exposed to fire is predicted with the use of advanced and simplified methods. The accurate modelling is based on heat transfer prediction and reduced stiffness, while the simplified methods are based on reduced cross-section method (RCSM) of EN 1995 1-2 (CEN, 2004). All methods are combined with a thick plate theory for laminates in order to compute the mid-span deflection of the floors. The more accurate modelling returned a better agreement with the experimental reference than RCSM approaches. Finally, a RCSM approach based on the time dependency of the zero stiffness layer is suggested.